Basic and Translational Research on Proteinase-Activated Receptors: Implication of Proteinase/Proteinase-Activated Receptor in Gastrointestinal Inflammation - Norimasa Yoshida; Toshikazu Yoshikawa (Elsevier, 2008)
Recently, the role of serine proteinases in the pathogenesis of inflammation and autoimmune diseases via interaction with the proteinase-activated receptor (PAR) has attracted attention. Activation of PAR has a pro-inflammatory effect through the overproduction of inflammatory cytokines such as interleukin (IL)-6 and IL-8. PAR2 activation in human esophageal epithelial cells by trypsin induces NFκB- and AP-1-dependent IL-8 production in association with activation of p38 MAPK and ERK1/2, suggesting that esophageal inflammation may be induced by PAR2 activation via reflux of trypsin. It has been also proposed that Helicobacter pylori (H. pylori) induces PAR expression in the gastric epithelial cells and H. pylori-derived serine proteinase promotes IL-8 production via PAR in the epithelial cells. In addition, an increase of PAR-dependent IL-8 production has been observed in H. pylori-infected human gastric mucosa, suggesting an important role for PAR2 in the modulation of gastric inflammation associated with H. pylori. Recent studies have strongly indicated that tryptase and PAR are implicated in the pathogenesis of inflammatory bowel disease and experimental colitis. We demonstrated that anti-tryptase therapy may become a new therapeutic strategy in human ulcerative colitis. Thus, the role of PAR in the gastrointestinal tract has been gradually clarified, but further investigations are needed because the receptor has a variety of functions. Keywords:: proteinase-activated receptor (PAR), esophagitis, Helicobacter pylori, colitis, proteinase inhibitor